UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN OPEN ENDED PADA SISWA KELAS VII SMP NUSANTARA BANDAR LAMPUNG - AB, Joko Sutrisno; Pratama, Elvandri Yogi (Epsilon: Jurnal Pendidikan Matematika, 2021)
Abstract: This research is a classroom action research which consists of three cycles. The purpose of this research is to improve mathematics learning outcomes by applying an open-ended approach. The subjects in this study were seventh grade students of SMP Nusantara Bandar Lampung in the even semester of the 2020/2021 school year. Each cycle consists of three meetings with two meetings for learning and one meeting for tests or evaluations. Data collection techniques used in this study using observation and test techniques. The data analysis technique was carried out by analyzing the results of observations and analysis of the results of the measurement test of learning outcomes. The results of data analysis showed an increase in student learning outcomes in each cycle. The percentage of students who got more than or equal to 70 in the first cycle was 41.93%, the second cycle was 51.61%, and the third cycle was 80.64%. Thus the percentage of students who scored more than or equal to 70 from cycle I to cycle II increased by 9.68%% and from cycle II to cycle III increased by 29.03%. The results obtained indicate that the application of an open-ended approach can improve students' mathematics learning outcomes.